Beyond Site Effects: Azimuthal Dependence of Ground Motion Residuals in the Volcanic Arc and Sedimentary Basins of West Java, Indonesia - Sudibyo, Reno; Wijayanto, Wijayanto; Gustono, Sandy Tri (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2026)
The complex tectonic setting of West Java, characterized by the interaction between the Sunda volcanic arc and deep sedimentary basins, presents significant challenges for seismic hazard assessment. This study recalibrates a local Ground Motion Prediction Equation (GMPE) using a hybrid regression strategy to isolate non-ergodic path effects. We implemented a constrained regression for Site Class C fixing the saturation parameter d = 5.80 to match the Class D baseline and applied site-term corrections for Class B. Our results reveal a weak correlation between residuals and  (R = 0.215), suggesting that shallow soil velocity is a suboptimal proxy for ground motion variability in this region. Instead, a distinct azimuthal anisotropy emerged, characterized by a dipolar residual pattern. Significant high-frequency attenuation (negative residuals) was identified in azimuths crossing the Quaternary Volcanic Arc, likely driven by multiple scattering in fractured magmatic media. Conversely, systematic amplification (positive residuals) was observed towards the Jakarta and Bandung Basins, consistent with deep basin resonance. These findings underscore the necessity of integrating azimuthal path terms into regional hazard models. Moving beyond 1D site-effect proxies is critical for enhancing the accuracy of Earthquake Early Warning (EEW) systems and urban seismic mitigation in West Java’s densely populated basins.